Iraqi women in Denmark : Ritual performance and belonging in everyday life - Pedersen, Marianne Holm (Book collections on Project MUSE., 2014)
An ethnographic study of ritual performance and place-making among Shi'a Muslim Iraqi women in Copenhagen. The book explores how Iraqi women construct a sense of belonging to Danish society through ritual performances, and investigates how this process is interrelated with their experiences of inclusion and exclusion in Denmark. The findings refute the all too simplistic assumptions of general debates on Islam and immigration in Europe that tend to frame religious practice as an obstacle to integration in the host society.